Enhanced Photocatalytic Activity of N/Li2MoO4 Co-Doped TiO2 Nanoparticles under Visible Light - Kwakkaew, Jutarat; Khangkhamano, Matthana; Kokoo, Rungrote; Sangchay, Weerachai (Applied Science and Engineering Progress, 2022)
TiO2-based nanomaterials have been extensively synthesized and used in a wide range of photocatalytic applications. However, the photocatalytic oxidation process, is only activated by irradiation with ultraviolet (UV) light, which limits its indoor applications. Herein, to improve such limitations, N/Li2MoO4-doped TiO2 nanoparticles were prepared via the sol-gel method. Li2MoO4 concentration was varied. The catalysts were characterized by XRD, XPS, FE-SEM, and UV-Vis spectroscopy. As-synthesized N/Li2MoO4-doped TiO2 catalysts exhibited their crystal sizes of as fine as 20 nm in diameter whereas that of the pure TiO2 was about 35 nm. The absorption ranges of the N/Li2MoO4-doped catalysts were relocated from the UV region toward the visible light region. The catalyst with 1 mol% Li2MoO4 offered the highest degradation rate of methylene blue (MB) solution upon visible light irradiation. Its fine crystal size, narrow band gap energy (2.82 eV), high defect concentration, and strong light absorption in the visible region are responsible for the enhanced photocatalytic activity of the 1 mol% Li2MoO4.